Prospects for the development of process equipment in aggregate-modular design for sustainable mechanical engineering - Yakovenko, Ihor; Permyakov, Alexander; Dobrotvorskiy, Sergey; Basova, Yevheniia; Kotliar, Alexey; Zinchenko, Artem (National Institute of Research and Development in Mechatronics and Measurement Technique, 2023)
The article analyses a wide range of existing technological systems for machining engineering production from special aggregate machines with rigid kinematic connection (control system) to portable machines with mechanisms of parallel structure, which are based on the aggregate-modular principle of the layout. The advantages and disadvantages of such equipment in the modern conditions of manufacturing development are considered in terms of their life cycle in the supply chain and the prospects for further implementation in the machine tool market. The authors analyze the contradictions between the performance and technological flexibility of machining systems and propose ways of resolving these contradictions on the basis of scientific achievements in the field of components, mechatronics, and CALS technologies. On the basis of the performed analysis, the authors suggest a concept and partially implemented a technique for creating various purpose machine-tool systems based on unified technological mechatronic modules considering the tendencies of modern machine-tool production to ensure the sustainability of enterprises under conditions of rapidly changing demand. The prospects of using augmented reality (AG) manufacturing tools for passportization of equipment and its components in order to optimize and green the life cycle of metal-cutting equipment have been substantiated.
Keywords: layout; interchangeability; competitiveness; efficient processing; conditioning; digitalisation; augmented reality